Adaptación y validación inicial de la versión española de la escala de pasión en el trabajo / Adaptation and Initial Validation of the Spanish Version of the Passion Scale in the Workplace - Orgambídez-Ramos, Alejandro; Borrego-Alés, Yolanda; Gonçalves, Gabriela (R.E.M.A. Revista electrónica de metodología aplicada, 2014)
ABSTRACT Passion is defined as a strong inclination toward an activity that people like, that they find important and in which they invest time and energy, such as working or playing football. Since a specific measure to assess levels of passion in the workplace is lacking in Spain, the aim of this study was to adapt and validate the Passion scale (Vallerand et al., 2003) into Spanish. After translating it from English to Spanish using the forward-backward translation method, it was given to a sample of 548 Spanish workers. Exploratory factor analyses were conducted to test the replicability of the scale. The results confirmed the expected two-factor structure through internal replication using exploratory factor analysis. Criterion-related validity was tested by correlating both obsessive and harmonious passion to work engagement. With regard to internal consistency, adequate Alpha coefficients were obtained for both factors.